2016
DOI: 10.1097/mjt.0000000000000018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Diagnosis, Viral PCR, and Antibiotic Utilization in Community-Acquired Pneumonia

Abstract: We evaluated the intensity of antibiotic therapy in patients in whom the etiology of community-acquired pneumonia (CAP) was determined using newly available diagnostic techniques. For 1 year, we studied all patients admitted for findings consistent with CAP. Sputum and blood cultures, urinary pneumococcal and Legionella antigens, and viral polymerase chain reaction (PCR) were studied prospectively. Patients were stratified based on the final diagnoses: proven bacterial, presumptive bacterial, viral, fungal, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…This finding was explained by being a new test [13]. In another study, Afzal et al [14] reported that a positive result for MRT decreased antibiotic use duration and prescription rate but the decrease in antibiotic prescription was not statistically significant. Timbrook et al [15] studied MRT in combination with PCT and concluded that a lower level of PCT and detection of virus by MRT were not associated with decreased use of antibiotics in RTIs, but in another study, a lower level of PCT in combination with detection of virus was found to be associated with shortened duration of antibiotic usage [16].…”
Section: Discussionmentioning
confidence: 98%
“…This finding was explained by being a new test [13]. In another study, Afzal et al [14] reported that a positive result for MRT decreased antibiotic use duration and prescription rate but the decrease in antibiotic prescription was not statistically significant. Timbrook et al [15] studied MRT in combination with PCT and concluded that a lower level of PCT and detection of virus by MRT were not associated with decreased use of antibiotics in RTIs, but in another study, a lower level of PCT in combination with detection of virus was found to be associated with shortened duration of antibiotic usage [16].…”
Section: Discussionmentioning
confidence: 98%
“…Studies conducted among pediatric populations have shown that rapid viral testing generally contributes to reducing antibiotic use [8][9][10], but those among adult patients have yielded conflicting results. Small reductions in antibiotic use, shorter durations of hospitalization, and lower overall costs were noted in some studies when test results were communicated to physicians rapidly [11][12][13][14]. However, these were limited by small sample sizes, by comparisons only to historical controls, or by the fact that they only included outpatients-making it difficult to extrapolate their results to acute care hospital settings.…”
mentioning
confidence: 99%
“…According to research, meta analysis comparing treatments, which lasted 7 days or less, as compared to treatments of 8 days or longer didn`t show differences in outcomes 14 . All the same, doctors have gradually increased treatment duration from 10 to 14 days 15,16 .…”
Section: Discussionmentioning
confidence: 99%